2012
DOI: 10.1097/tp.0b013e318239e90c
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of T-Lymphocyte Subsets and Posttransplant Opportunistic Infections in Heart and Kidney Transplant Recipients

Abstract: Determination of T-lymphocyte subsets is a simple and effective parameter to identify patients at risk of developing OIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 44 publications
7
44
0
Order By: Relevance
“…The most common OI after RTx was CMV related, accounting for approximately half of these infections; this finding is supported by other studies (26)(27)(28). Urinary tract infections accounted for the majority of SIs in our study and have also been described by previous studies (29)(30)(31).…”
Section: Discussionsupporting
confidence: 81%
“…The most common OI after RTx was CMV related, accounting for approximately half of these infections; this finding is supported by other studies (26)(27)(28). Urinary tract infections accounted for the majority of SIs in our study and have also been described by previous studies (29)(30)(31).…”
Section: Discussionsupporting
confidence: 81%
“…Calarota et al 26 regularly assessed the CD4 þ and CD8 þ T-cell numbers during the first 8 months after kidney and heart transplantation and reported that those patients who developed opportunistic infections had lower counts as compared with those without. Various authors as well have consistently shown that the risk of various intercurrent infections after kidney transplantation is increased in recipients with low CD4 þ T-cell counts.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated the kinetics of T-lymphocyte subsets and their association with infections after transplantation [3][4][5][6]. Patients with low CD4 + T-cell counts at 1 month after heart transplantation showed poor recovery of CD4 + T cells and developed OI, while low (and poor recovery of) CD8 + T-cell counts were associated with the risk of OI in kidney transplant recipients (KTR) [4]. Similarly, a more recent study has confirmed that low T-cell counts at month 1 posttransplant predicts the subsequent occurrence of OI in KTR [6].…”
Section: Enumeration Of T-cell Subsetsmentioning
confidence: 99%